Review of kenaf fiber reinforced polymer composites - Ab. Rashdi, Abdalla A.; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Abdan, Khalina (Industrial Chemistry Research Institute, 2009)
General characteristics of kenaf fibers and mechanical properties of its polymer composites (dependently on the environmental conditions) as well as applications directions of such materials have been presented.